Potassium Iodide-Modified Lead-Free Cs3Bi2I9 Perovskites for Enhanced High-Efficiency Solar Cells - Shindume Lomboleni Hamukwaya; Huiying Hao; Melvin Mununuri Mashingaidze; Tingting Zhong; Shu Tang; Jingjing Dong; Jie Xing; Hao Liu (Nanomaterials, 2022)
Lead-free, bismuth-based perovskite solar cells (PSCs) are promising, non-toxic, and stable alternatives to lead-based PSCs, which are environmentally harmful and highly unstable under deprived air conditions. However, bismuth-based PSCs still suffer from low-power-conversion efficiency (PCE) due to their large bandgap and poor film morphology. Their poor film-forming ability is the greatest obstacle to Cs₃Bi₂I₉ progress in thin-film solar cell technology. This study synthesizes novel, lead-free perovskites with a small bandgap, excellent stability, and highly improved photovoltaic performance by integrating different amounts of potassium iodide (KI) into a perovskite precursor solution. KI incorporation improves the crystallinity of the perovskite, increases the grain size, and decreases the potential contact distribution, which is demonstrated by X-ray diffraction, electronic scanning microscopy, atomic force microscopy, and ultraviolet-visible spectroscopy. The Cs₃Bi₂I₉ PSC device with 2 vol. % incorporation of KI shows the highest PCE of 2.81% and Voc of 1.01 V as far as all the Bi-based cells fabricated for this study are concerned. The study demonstrates that incorporating KI in the Cs₃Bi₂I₉ perovskite layer highly stabilizes the resultant PSC device against humidity to the extent that it maintains 98% of the initial PCE after 90 days, which is suitable for solar cell applications. The devices also demonstrate greater resistance to airborne contaminants and high temperatures without encapsulation, opening up new possibilities for lead-free Cs₃Bi₂I₉ PSCs in future commercialization.